Implementing Project-Based Learning (PBL) in Final Collection to Improve the Quality of Fashion Design Student - Indarti, Indarti (INVOTEC, 2016)
Fashion design education is one of education that prepares students to work in fashion design field. Students research future fashion trends, sketch designs, select colors, fabrics and patterns, and give instructions on how to make the products they designed. Fashion design education not only nurture and develop student’s creative skills, it also teaches essential practical skills such as production techniques and material properties, to create a final product. According to this, new educational methods and strategies are needed in order engage students in the learning process and guarantee higher quality. Project-based learning (PBL) is example of educational approach that takes in account student-center learning. Project based learning (PBL) provides opportunities for students to build these qualities, as well as more deeply learn traditional academic content and understand how it applies to the real world. The methods of Literature review will apply in this research. Literature searches process through journal, proceeding and book. Literature searches are also undertaken most using computer and electronic databases. PBL methodology enhances students learning and improves students’ confident, technical skill, soft skill and prepare graduate for professional practice. The benefit of implementing PBL are increase team work skill and student motivations, articulation between theory and practice, inquiry and problem solving.